Cerebral toxoplasmosis with neurological co-infection in people living with AIDS/HIV: results of a prospective cohort in São Paulo, Brazil - João Paulo Marochi Telles; José Ernesto Vidal (Arquivos de Neuro-Psiquiatria, 2023)
Background Concomitant neurological diseases in people living with HIV/AIDS (PLWHA) is a challenging subject that has been insufficiently evaluated by prospective clinical studies. The goal of the present study was to identify the clinical characteristics and outcomes of PLWHA with cerebral toxoplasmosis and neurological co-infections. Methods We conducted a prospective observational cohort study at a tertiary teaching center in São Paulo, Brazil, from January to July 2017. Hospitalized PLWHA aged ≥ 18 years with cerebral toxoplasmosis were consecutively enrolled. A standardized neurological examination was performed at admission and weekly until discharge or death. Diagnosis and treatment followed institutional routines; neuroradiology, molecular diagnosis, neurosurgery, and the intensive care unit (ICU) were available. The main outcomes were neurological coinfections and in-hospital death. Results We included 44 (4.3%) cases among 1,032 hospitalized patients. The median age was 44 (interquartile range [IQR]: 35–50) years, and 50% (n = 22) of the patients were male. The median CD4+ T lymphocyte count was of 50 (IQR: 15–94) cells/mm3. Multiple lesions on computed tomography were present in 59% of the cases. Neurological coinfections were diagnosed in 20% (n = 9) of the cases, and cytomegalovirus was the most common etiology (encephalitis: n = 3; polyradiculopathy: n = 2). Longer hospital stays (30 versus 62 days; p = 0.021) and a higher rate of ICU admissions (14% versus 44%; p = 0.045) were observed among PLWHA with neurological coinfections in comparison to those without them. The rate of in-hospital mortality was of 13.6% (n = 6) (coinfection group: 33%; no coinfection group: 8.6%; p = 0.054). Conclusion Neurological c-infections were common among PLWHA with cerebral toxoplasmosis, and cytomegalovirus was the main copathogen. The group of PLWHA with neurological co-infections underwent longer hospital stays and more frequent intensive care unit admissions. Additionally, this group of patients tended to have higher in-hospital mortality rate.